Modelling renal defects in Bardet-Biedl syndrome patients using human iPS cells - Williams, James; Hurling, Chloe; Munir, Sabrina; Harley, Peter; Machado, Carolina Barcellos; Cujba, Ana-Maria; Alvarez-Fallas, Mario; Danovi, Davide; Lieberam, Ivo; Sancho, Rocio; Beales, Philip; Watt, Fiona M. (Frontiers in Cell and Developmental Biology, 2023)
Bardet-Biedl syndrome (BBS) is a ciliopathy with pleiotropic effects on multiple tissues, including the kidney. Here we have compared renal differentiation of iPS cells from healthy and BBS donors. High content image analysis of WT1-expressing kidney progenitors showed that cell proliferation, differentiation and cell shape were similar in healthy, BBS1, BBS2, and BBS10 mutant lines. We then examined three patient lines with BBS10 mutations in a 3D kidney organoid system. The line with the most deleterious mutation, with low BBS10 expression, expressed kidney marker genes but failed to generate 3D organoids. The other two patient lines expressed near normal levels of BBS10 mRNA and generated multiple kidney lineages within organoids when examined at day 20 of organoid differentiation. However, on prolonged culture (day 27) the proximal tubule compartment degenerated. Introducing wild type BBS10 into the most severely affected patient line restored organoid formation, whereas CRISPR-mediated generation of a truncating BBS10 mutation in a healthy line resulted in failure to generate organoids. Our findings provide a basis for further mechanistic studies of the role of BBS10 in the kidney.